Test–retest Reliability and Construct Validity of an Online and Paper Administered Physical Activity Neighborhood Environment Scale (PANES). Issue 1 (2nd January 2020) - Frehlich, Levi; Blackstaffe, Anita; McCormack, Gavin R.
ABSTRACT: The Physical Activity Neighborhood Environment Scale (PANES) has been used internationally; however, PANES properties have not been assessed in all geographical contexts. Our objectives were to assess the reliability and validity of an online and paper version of the PANES in Canadian adults. Reliability was estimated using intraclass correlation coefficients ( ICC ), percent of overall agreement ( p0 ) and Cohen's Kappa coefficient ( κ ). Lower 95% confidence interval (CI) ICC ranged from 0.10 to 0.70. Lower 95%CI for κ statistics ranged from −0.20 to 0.64 and p0 ranged from 80.1% to 95.7%. Cronbach's alpha coefficients ( α ) estimated internal consistency of the PANES (α = 0.58 for the paper version and α = 0.55 for the online version). Mean scores for the PANES Built Environment Index (BEI) significantly differed by neighborhood street pattern ( p < .05). The PANES administrated via paper or online provides reliable overall agreement and valid estimates of the self-reported neighborhood built environment supportiveness of physical activity.